Pengembangan Manajemen Sekolah Terintegrasi Berbasis Sistem Informasi di Sumatera Utara - Rahmadi, Fuji; Munisa, Munisa; Rozana, Salma; Rangkuti, Charles; Ependi, Rustam; Harianto, Eko (Fitrah: Journal of Islamic Education, 2021)
This study aims to analyze the application of an integrated information system in educational institutions, and the impact of the application of an education management information system on ethics and society. This research was conducted in three different locations, namely Medan City, Binjai City, and Asahan Regency. This research uses qualitative research methods, with data collection techniques using observation, interviews, and documentation studies. The results of the study explain that the application of an integrated information system developed by PT. Engineering Technology Metromatics uses the edulink application. This application is a school management-based application that can help educational institutions to create a learning environment and management activities to be more effective and efficient. By using this information system application, all data about the development of students will be recorded digitally, so that the actions that will be taken by teachers or parents/guardians of students in dealing with student problems can be about the substance of the problems faced by students. Through this information system, the track record of students will be clearly identified, so that actions in solving student problems can be carried out on target, effectively and efficiently. This application has a positive impact on teachers, especially in identifying and recording all attitudes and attitude assessments so that they can be the basis for developing student attitudes.